Hereditary hemochromatosis and transferrin receptor 2 - Chen, Juxing; Enns, Caroline A. (Biochimica et biophysica acta, 2012)
Multicellular organisms regulate the uptake of calories, trace elements, and other nutrients by complex feedback mechanisms. In the case of iron, the body senses internal iron stores, iron requirements for hematopoiesis, and inflammatory status, and regulates iron uptake by modulating the uptake of dietary iron from the intestine. Both the liver and the intestine participate in the coordination of iron uptake and distribution in the body. The liver senses inflammatory signals and iron status of the organism and secretes a peptide hormone, hepcidin. Under high iron or inflammatory conditions hepcidin levels increase. Hepcidin binds to the iron transport protein, ferroportin (FPN), promoting FPN internalization and degradation. Decreased FPN levels reduce iron efflux out of intestinal epithelial cells and macrophages into the circulation. Derangements in iron metabolism result in either the abnormal accumulation of iron in the body, or in anemias. The identification of the mutations that cause the iron overload disease, hereditary hemochromatosis (HH), or iron-refractory iron-deficiency anemia has revealed many of the proteins used to regulate iron uptake. In this review we discuss recent data concerning the regulation of iron homeostasis in the body by the liver and how transferrin receptor 2 (TfR2) affects this process. TfR2 plays a key role in regulating iron homeostasis in the body. The regulation of iron homeostasis is important. One third of the people in the world are anemic. HH is the most common inherited disease in people of Northern European origin and can lead to severe health complications if left untreated. This article is part of a Special Issue entitled Transferrins: Molecular mechanisms of iron transport and disorders. ► Recent data concerning the regulation of iron homeostasis in the body by the liver is discussed. ► Transferrin receptor 2 plays a distinct role in the regulation of hepcidin. ► Transferrin receptor 2 is controlled both transcriptionally and posttranscriptionally at the level of protein stability. ► Transferrin receptor 2 also plays a role in erythropoiesis. ► The regulation of hepcidin transcription is controlled by both iron through Tf saturation and BMP6 and by inflammation.